Verbal Bullying - Jennifer Rivkin
Studies indicate that verbal bullying is more than twice as common as physical bullying. It occurs across all age groups, genders, economic classes, and ethnic groups. Verbal bullying can inflict long-term emotional scars. This informative title examines the causes and consequences of verbal bullying. Readers will learn to identify different kinds of verbal bullying and discover concrete strategies to prevent it.